Gene-level connections between anxiety disorders, ADHD, and head and neck cancer: insights from a computational biology approach - Lian, Meng; Li, Haiyang; Zhang, Zhiyang; Fang, Jugao; Liu, Xiaoqin (Frontiers in Psychiatry, 2025)
BackgroundAnxiety disorders (AD), ADHD, and head and neck cancer (HNC) are complex conditions with potential genetic interconnections that remain to be fully elucidated. The purpose of this study is to investigate gene-level connections among ADHD, AD, and HNC.MethodA comprehensive literature mining approach identified potential gene-disease relationships from PubMed and bioinformatics databases, analyzing 19,924 genes. An AI-driven computational process constructed a gene-disease relationship table using the Adjusted Binomial Method Algorithm (ABMA) to evaluate association reliability. Overlapping genes were analyzed through protein-protein interaction (PPI) networks, functional annotations, and literature-based pathway analyses to elucidate shared and unique genetic mechanisms linking these diseases.ResultsThe analysis identified 141 significant genes associated with AD, 153 with ADHD, and 1,065 with HNC (q-value < 0.05). These genes demonstrated significant overlap (odds ratio ≥ 1.8; p ≤ 2.58E-2) and high interconnectivity (PPI network density ≥ 0.39, clustering coefficient ≥ 0.76, and diameter ≤ 3). Centrality analysis revealed core genes such as IL-6, MYC, NLRP3, and CXCR4 as critical mediators. Functional enrichment analysis identified key pathways, including serotonergic synapse, inflammatory response, and Toll-like receptor signaling, highlighting the involvement of neuronal and immune mechanisms. Functional pathway analysis demonstrated reciprocal genetic influences among AD, ADHD, and HNC, emphasizing shared and distinct gene-level connections that may underlie their co-occurrence and mutual risk factors.ConclusionThis study reveals a complex and interconnected genetic network among AD, ADHD, and HNC, highlighting shared pathways, unique mechanisms, and critical genes, providing valuable insights into the genetic underpinnings of these conditions and potential avenues for therapeutic exploration.